Sustainable strategies for managing Brassica napus (oilseed rape) resistance to Leptosphaeria maculans (phoma stem canker) Under the aegis of a European-Australian workshop held at INRA, Versailles, France, in association with the EU SECURE project (QLK5-CT-2002-01813) - Fitt, B. D. L.; Evans, N.; Howlett, B. J.; Cooke, B. M.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
The interaction between the fungus Leptosphaeria maculans and oilseed rape (Brassica napus) is becoming an excellent model system for studying genetics of host-pathogen interactions. Leptosphaeria maculans causes phoma stem canker (blackleg) on oilseed rape and other Brassica crops worldwide. Recently, application of molecular techniques has led to increased understanding of the genetics of this hemibiotrophic interaction. The complete sequences of the genomes of L. maculans and B. rapa (comprising the Brassica A genome) will be available soon. This will provide new opportunities to investigate basic metabolic pathways in the host and the pathogen, and detailed knowledge of the disease process. Worldwide, the major strategy for control of phoma stem canker is the use of cultivars with resistance to L. maculans. However, serious epidemics have occurred recently in Australia and Europe when L. maculans populations changed such that major gene resistance in oilseed rape was overcome. Thus there is an urgent need to find and deploy sources of resistance to L. maculans in a manner that enhances their durability. This book provides researchers with a synthesis of the recent studies relating to strategies for management of resistance genes to provide effective control of L. maculans, and will stimulate further research on this important model system.
World-wide importance of phoma stem canker (Leptosphaeria maculans and L. biglobosa) on oilseed rape (Brassica napus) -- Genetic linkage maps and genomic organization in Leptosphaeria maculans -- Major gene resistance in Brassica napus (oilseed rape) is overcome by changes in virulence of populations of Leptosphaeria maculans in France and Australia -- Major gene and polygenic resistance to Leptosphaeria maculans in oilseed rape (Brassica napus) -- A large-scale survey of races of Leptosphaeria maculans occurring on oilseed rape in France -- Frequency of avirulence alleles in field populations of Leptosphaeria maculans in Europe -- Fitness cost associated with loss of the AvrLm4 avirulence function in Leptosphaeria maculans (phoma stem canker of oilseed rape) -- Improved resistance management for durable disease control: A case study of phoma stem canker of oilseed rape (Brassica napus) -- Durability of resistance and cost of virulence -- Dissemination of information about management strategies and changes in farming practices for the exploitation of resistance to Leptosphaeria maculans (phoma stem canker) in oilseed rape cultivars.
Keywords: Life sciences; Agriculture; Plant science; Botany; Plant pathology; Life Sciences; Plant Pathology; Plant Sciences; Agriculture; Electronic books